Does gene expression analysis inform us in rheumatoid arthritis?. (7th December 2009) - Häupl, T; Stuhlmüller, B; Grützkau, A; Radbruch, A; Burmester, G-R
Abstract : Transcription profiling has become a standard technology in research. It is mainly applied in the search for biomarkers to improve diagnostic and prognostic classification, to quantify disease activity and to predict or indicate response to therapy. This review will focus on rheumatoid arthritis and discuss considerations for sample selection, prerequisites for functional interpretation of data and the current status of information deduced in the field of biomarkers for the various clinical questions. In the next few years, prediction of response to treatment is the most important aim of biomarker research. With the growing number of new biological agents, there is increasing pressure to identify molecular parameters that will not only guide the therapeutic decision but also help to define the most important targets for which new biological agents should be tested in clinical studies.